Enhancement of Power System Stability using FACTS devices - Kakaiya, Shailesh U; Cephas, Okumu; Paichaure, Geeta N; Parekh, Bhupendra R (International Journal of Computer Sciences and Engineering, 2018)
The dynamic system damping can be measured by using the rate of dissipation of transient energy. This paper deals with the different control methods for minimizing unwanted electromechanical perturbations and disturbances in power system with STATCOM (Static Compensator), SSSC (Static Synchronous Series Capacitor), and UPFC (Unified Power Flow Controller). A SMIB (Single Machine Infinite Bus) was simulated under several variations of situations. The results concluded depicts the functionality and robustness of these devices on power system stability.